2015
DOI: 10.3109/13813455.2014.985686
|View full text |Cite
|
Sign up to set email alerts
|

Association of VNTR polymorphisms inDRD4, 5-HTTandDAT1genes with obesity

Abstract: As a conclusion, there was no association between 5-HTT, DAT1 and DRD4 genes VNTR polymorphisms and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…However, these results differ from those studies reporting the S allele associated with higher BMI (Fuemmeler et al, 2008, Sookoian et al, 2008, or reporting no associations between 5-HTTLPR and obesity traits (Mergen et al, 2007;Hamed et al, 2015). Regarding the VNTR STin2 in the second intron of SLC6A4 gene, only one recent study has investigated the association with obesity and no significant results were observed (Uzun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results differ from those studies reporting the S allele associated with higher BMI (Fuemmeler et al, 2008, Sookoian et al, 2008, or reporting no associations between 5-HTTLPR and obesity traits (Mergen et al, 2007;Hamed et al, 2015). Regarding the VNTR STin2 in the second intron of SLC6A4 gene, only one recent study has investigated the association with obesity and no significant results were observed (Uzun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Primers for the 5-HTTLPR polymorphism were described in Gelernter et al (1997), (JP 5'-ATGCCAGCACCTAACCCCTAATGT-3' and GR 5'-GGACCGCAAGGTGGGCGGGA-3'. For STin2 the PCR amplification of the 17-bp VNTR region located in intron 2 of SLC6A4 was performed from genomic DNA using forward 5'-GGTCAGTATCACAGGCTGCGAGTAG-3' and reverse 5'-TGTTCCTAGTCTTACGCCAGTGAAG-3' primers described in Uzun et al (2015). The VNTR in MAOA gene was studied using the primers 5'-ACAGCCTGACCGTGGAGAAG-3' (forward) and 5' -GAACGTTGACGCTCCCGGA -3' (reverse), as described in Sabol et al (1998).…”
Section: Genotypingmentioning
confidence: 99%
“…Borkowska et al detected association of the S allele with development of depressive temperament while the L allele was associated with greater obesity and prevalence of depression in Polish adults [113]. There was no significant association observed between 5-HTTLPR and BMI status in Turkish studies [114, 115]. …”
Section: Main Textmentioning
confidence: 99%
“…The first study which investigated the association between STin2 VNTR and obesity found no significant effect on obesity in Turkish adults [115]. However, when combined with 5-HTTLPR, the L/10 allele haplotype showed a significant association with overweight/obesity in Portuguese adults [116].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation